Associações interespecíficas em aves florestais de terra firme: uma análise quantitativa com comparação de técnicas de observação direta - Fernández Arellano, Gilberto Josimar (Instituto Nacional de Pesquisas da Amazônia - INPA, 2015)
Abstract Heterospecific associations of terra firme birds forest: a quantitative analysis with comparative indirect observation techniques Birds participates in different types of mono and heterospecific groups in several geographical regions. Heterospecific groups are clusters of individuals from at least two or more species that depend on any available resource (aggregations) or reciprocal interaction (mixed flocks). Ant-following birds are an example of aggregations based on resource (e.g. army ants, Eciton burchelli). Mixed-species bird flocks are an example of group whose formation and cohesion depends on the presence of another bird. The study of these two types of groups, however, faces some sampling biases. Searching for focal species that determine a priori the presence of the flock and participating species is the main bias to consider. In this study we used mist- nets, autonomous recorders, randomization process and social networks as a new approach to collecting, analyzing and presenting species associations degree data. A set of 44 species were combined to construct all possible pairs of species which were later evaluated by comparing with null models. Thus, 23 of the 44 focal species were most frequently associated with, or formed pair of species whose association index were more extreme than expected by chance. Furthermore, 18 of the 23 species were more frequently associated with mixed-species flocks, whereas just one pair of species are ant-followers. Thirteen of the 18 species was appointed as constants members of mixed flocks, whereas just one pair of species (Gymnopithys rufigula and Pithys albifrons) was appointed as professional army-ant-followers. Finally, 8 of the 13 species have been otherwise detected using both techniques, or there is no correlation between the association index of these pairs of species. The pattern of association for pairs of species, however, could also be attributed to the effects of sampling. In the present study, therefore, we suggest the presence of some ecological process influencing the pattern of association or co-occurrence between species. Key-words: mixed flocks, ant-following birds, autonomous recorders, mist-nets, frequency of co-detecction.
Keywords: Bandos mistos; Seguidores de formiga; Coocorrência de espécies